MOTIVATIONAL STRATEGIES FOR GENERATING ENTHUSIASM OF INDONESIAN EFL LEARNERS - Salwa Salwa (Jurnal Inspirasi Pendidikan, 2014)
The issue of motivation, especially in EFL context is very important since motivation is considered as the fuel or the driving force to keep a language class ‘alive’. Motivation itself is defined as the learners’ orientation with regard to the goal of learning a second language. Compared to ESL context, learning English in the EFL setting needs more efforts and persistence since English is not used in daily communication and there is little opportunity to interact with native English speakers.. This paper is going to discuss some motivational strategies to boost Indonesian EFL learners’ enthusiasm in learning English as a foreign language. Keywords : motivation, EFL learners, language class